Designing a framework for materials flow by integrating circular economy principles with end-of-life management strategies - Huang, Yuan; Shafiee, Mahmood; Charnley, Fiona; Encinas-Oropesa, Adriana (MDPI, 2022)
Circular economy is an upward trending notion that has drawn worldwide attention of policymakers, industry administrators, environmentalist as well as academic researchers. Though there are several tools developed for monitoring the material recovery, a very few number of research have been conducted to integrate circular economy principles with end-of-life (EOL) management strategies. This paper proposes an EOL-driven circular economy framework for the management of materials flow so as to extend the lifetime of materials through improved durability as well as to provide more social, economic and environmental benefits through less material waste. A case study from the agricultural waste industry is presented in order to test the model and validate its performance. The results show that the proposed framework has a good potential for small and medium enterprises (SME) advances.
Keywords: sustainability; circular economy; end-of-life management; agricultural waste management; materials recovery